2001
DOI: 10.1046/j.1442-2026.2001.00185.x
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin toxicity in the emergency department: Recommendations for management

Abstract: Objective: To examine patients who presented to a hospital emergency department with evidence of warfarin toxicity, and to review the available published literature to determine what guidelines are available for management of this problem. Method: A retrospective analysis of all adult patients who presented to The Geelong Hospital Emergency Department between 1 January 1996 and 30 June 1998 with international normalized ratio > 6 due to warfarin toxicity. Results: A total of 84 patients with international norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Consequently, administration of these products has to be made with respect of a narrow therapeutic index, is delicate and needs regular medical control to avoid risks of haemorrhage [1,2]. Indeed, the therapeutic overdose can be at the origin of particularly serious hemorrhagic accidents, causing death in case of late medical intervention [3].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, administration of these products has to be made with respect of a narrow therapeutic index, is delicate and needs regular medical control to avoid risks of haemorrhage [1,2]. Indeed, the therapeutic overdose can be at the origin of particularly serious hemorrhagic accidents, causing death in case of late medical intervention [3].…”
Section: Introductionmentioning
confidence: 99%
“…Cruickshank et al5 reported that severe hemorrhage, at about 1.0-3.0% and light hemorrhage at about 4.8-9.5%, occur in warfarin-dosed patients each year. Landelfeld and Beyth reported that the risk of hemorrhage in the group of patients who received warfarin treatment was 0.6-9.6%, which is five times higher than that in a group of those without warfarin administration 6…”
Section: Discussionmentioning
confidence: 99%
“…Overdoses of vitamin K antagonists, accidental or otherwise, and destabilization of the INR are not uncommon, and account for a significant number of unnecessary deaths. 36 The standard approach for such patients depends on whether they present with active bleeding or whether their INR is too high. For the non-bleeding patient whose INR is supratherapeutic, temporary discontinuation of the oral anticoagulant may suffice.…”
Section: Reversal Of Anticoagulationmentioning
confidence: 99%